Yayasan Sarawak World Style English Debate Challenge Trophy 2008 - Ghazali, Azlina; Saba, Siniter (Universiti Teknologi MARA, Sarawak, 2009)
Ten universities from both private and public institutions of higher learning throughout Sarawak participated in the World Style Debate while twenty-two representatives from the universities contested in the public speaking competition, which were held concurrently. With the objective of nurturing young people to converse confidently and effectively in the English Language as well as generating critical and creative thinking, it is hope that undergraduates who acquire these vitally important skills will sail through their studies without any difficulty.